History Teaches Us That Confronting Antibiotic Resistance Requires Stronger Global Collective Action. Issue 3 (June 2015) - Podolsky, Scott H.; Bud, Robert; Gradmann, Christoph; Hobaek, Bård; Kirchhelle, Claas; Mitvedt, Tore; Santesmases, María Jesús; Thoms, Ulrike; Berild, Dag; Kveim Lie, Anne
<x xml:space="preserve">Abstract</x> Antibiotic development and usage, and antibiotic resistance in particular, are today considered global concerns, simultaneously mandating local and global perspectives and actions. Yet such global considerations have not always been part of antibiotic policy formation, and those who attempt to formulate a globally coordinated response to antibiotic resistance will need to confront a history of heterogeneous, often uncoordinated, and at times conflicting reform efforts, whose legacies remain apparent today. Historical analysis permits us to highlight such entrenched trends and processes, helping to frame contemporary efforts to improve access, conservation and innovation.